Analyzing Enterprise Risk Management’s Determinants and Their Impact to Market Valuation - Suryady, Ardi Tjiang Y; Daromes, Fransiskus Eduardus; Ng, Suwandi (Institut Transparansi dan Akuntabilitas Publik (INSPIRING), 2025)
Purpose – This research investigates the role of managerial ability in creating market valuation through corporate innovative success and enterprise risk management. Design/methodology/approach – This research was built with Resource-based View Theory and Stakeholder Theory. This research uses secondary data in the form of financial reports and annual reports and sample selected using the purposive sampling method. Findings – The results of this research show that managerial ability has a positive and significant influence on corporate innovative success. The findings of this research also found that corporate innovative success has a positive and significant influence on enterprise risk management. Apart from that, the results of this research also show that enterprise risk management has a positive and significant influence on market valuation. Finally, this research finds that corporate innovative success and enterprise risk management do not mediate the relationship between managerial ability and market valuation. Originality/value - The population used in this research is all non-financial companies listed on the Indonesia Stock Exchange (BEI) during the 2021-2023 period. Keywords: Managerial Ability, Corporate Innovative Success, Enterprise Risk Management, Market Valuation Paper type Research Result